Passively Q-switched erbium-doped fiber laser based on graphene oxide as saturable absorber - Mansoor, A. K. W.; Hamida, Belal Ahmed; Eltaif, Tawfig; Ismail, Ezzatul Irradah; Abdul Kadir, Nor Aishah; Khan, Sheroz; Harun, Sulaiman Wadi (Journal of Optical Communications., 2017)
In this paper, passively Q-switched fiber laser is demonstrated and the laser output energy is stabilized by using 2.4 m Erbium-doped fiber laser (EDFL) with a graphene oxide used as saturable absorber (GO-SA). According to the experimental results in the Q-switched configuration, the laser cavity emits a wavelength centered at 1,558.75nm, and by inserting the GO-SA into EDFL cavity, hence, the laser output energy around 1.68nJ with an FWHM pulse width of 2.3μs at 123.5kHz was achieved.